Assisted Tandem Catalysis: Metathesis Followed by Asymmetric Hydrogenation from a Single Ruthenium Source. Issue 10 (6th July 2015) - Renom‐Carrasco, Marc; Gajewski, Piotr; Pignataro, Luca; de Vries, Johannes G.; Piarulli, Umberto; Gennari, Cesare; Lefort, Laurent
Abstract Here we report the first example of a tandem metathesis–asymmetric hydrogenation protocol where the prochiral olefin generated by metathesis is hydrogenated with high enantioselectivity by an in situ formed chiral ruthenium catalyst. We show that either the ruthenium metathesis catalysts or the ruthenium species formed during the metathesis reaction can be converted into an efficient asymmetric hydrogenation catalyst upon addition of a chiral ligand and an alcohol. The performance in asymmetric hydrogenation appears to be very dependent on the solvent, the chiral ligand, and the prochiral substrate.